Respuesta :

Answer:

Step-by-step explanation:

1). f(x) = x² - 9

   g(x) = x - 3

   h(x) = f(x) ÷ g(x)

          = [tex]\frac{x^2-9}{x-3}[/tex]

          = [tex]\frac{(x+3)(x-3)}{(x-3)}[/tex]

          = (x + 3)

2). f(x) = x² - 4x + 3

         = x² - 3x - x + 3

          = x(x - 3) - 1(x - 3)

          = (x - 1)( x- 3)

    g(x) = x - 3

   h(x) = f(x) ÷ g(x)

          = [tex]\frac{(x-1)(x-3)}{(x-3)}[/tex]

          = (x - 1)

3). f(x) = x² + 4x - 5

          = x² + 5x - x - 5

          = x(x + 5) - 1(x + 5)

          = (x - 1)(x + 5)

    g(x) = x - 1

    h(x) = f(x) ÷ g(x)

           = [tex]\frac{(x-1)(x+5)}{(x-1)}[/tex]

           = (x + 5)

4). f(x) = x² - 16

          = (x - 4)(x + 4) [Since a² - b² = (a - b)(a + b)]

   g(x) = (x - 4)

   h(x) = f(x) ÷ g(x)

          = [tex]\frac{(x-4)(x+4)}{(x-4)}[/tex]

          = (x + 4)

Answer:

Step-by-step explanation:

1). f(x) = x² - 9

  g(x) = x - 3

  h(x) = f(x) ÷ g(x)

         =

         =

         = (x + 3)

2). f(x) = x² - 4x + 3

        = x² - 3x - x + 3

         = x(x - 3) - 1(x - 3)

         = (x - 1)( x- 3)

   g(x) = x - 3

  h(x) = f(x) ÷ g(x)

         =

         = (x - 1)

3). f(x) = x² + 4x - 5

         = x² + 5x - x - 5

         = x(x + 5) - 1(x + 5)

         = (x - 1)(x + 5)

   g(x) = x - 1

   h(x) = f(x) ÷ g(x)

          =

          = (x + 5)

4). f(x) = x² - 16

         = (x - 4)(x + 4) [Since a² - b² = (a - b)(a + b)]

  g(x) = (x - 4)

  h(x) = f(x) ÷ g(x)

         =

         = (x + 4)